Contraceptive Practice of Married Women: Experience from a Rural Community of Bangladesh (Anwer Khan Modern Medical College Journal, 2014)
Bangladesh is a country having high density of population in the world. Its fertility rate ranges from 4.1 to 5.49 and life expectancy is 66years while the total fertility rate of Asia is 2.2 and life expectancy 70 years. This descriptive type of cross sectional survey was carried out among 240 married women of reproductive age from July to December, 2012 in some villages of Keranigonj, Upazila, Dhaka. 73(31%) were practicing some methods of contraception, while 167 (69%) were not using it. OCP (Oral Contraceptive Pill) was the commonest method of contraception followed by Condoms 12(5%), Injectable 12(5%), Implant 12(5%) & Tubectomy 6(3%). None was found using IUCD and Traditional method ( withdrawal, rhythm method ) and emergency contraceptive method. The use of contraceptive was more common in grand multipara (p35 years old ladies (p